Beyond the subterranean energy regime? Fuel, land use and the production of space. Issue 4 (29th May 2017) - Huber, Matthew T; McCarthy, James
Abstract : In this paper, we argue that energy should be seen as a critical aspect of changing historical regimes in the social production of space. We suggest the common definition of energy as the 'capacity to do work' ignores key aspects of the space required for energy in the first place (particularly the concept of power density). Articulating the basic spatial concept of power density with a historical–geographical materialist understanding of energy regimes, we argue that industrial capitalism is defined by an intensive vertical reliance upon subterranean stocks of energy that require relatively little surface land to harness. Previous modes of production were characterised by a more 'horizontal' reliance upon extensive territory (e.g. forests) to meet fuel needs. While attentive to the spatialities of overall energy complexes, we focus in particular on how the spatialities of energy sources affect the production of space in major and distinctive ways. Drawing from environmental and economic history, we argue the use of fossil fuels ushered in a 'subterranean energy regime' that not only relied on underground stocks of energy, but substantially relieved the societal demand for land‐based and spatially extensive sources of fuel (i.e. wood and other organic sources). The use of subterranean fuel (first coal) not only powered machines, but revolutionised 'heat‐process' industries like iron smelting that dramatically expanded the steel and other metal industries; thus, transforming the built environment. We then consider the spatial and land‐use implications of a transition away from this subterranean regime to renewable energy sources (solar and wind). A return to the surface for energy would not be biological as in pre‐industrial times, but industrial in the sense that these systems require industrial production. Moreover, the spatially extensive nature of such energy technologies should raise important political questions about existing land‐use patterns and livelihoods, particularly in rural areas.